Comparison of esophageal stent placement versus endoscopic incision method for treatment of refractory esophageal anastomotic stricture - Wu, Peiyao; Wang, Fei; Wu, Xiaochao; Nie, Junjie; Ge, Xianxiu; Li, Quanpeng; Lin, Jie; Miao, Lin (Annals of Palliative Medicine; Vol 8, No 4 (September 27, 2019): Annals of Palliative Medicine, 2019)
Background: Refractory esophageal anastomotic strictures are difficult to treat. Current treatments include esophageal stent placement (ESP) and the endoscopic incision method (EIM). This study was conducted to determine which treatment is better for patients with refractory esophageal anastomotic stricture. Methods: This study retrospectively collected data of patients with refractory esophageal anastomotic stricture who underwent ESP or EIM between January 2012 and June 2018. Dysphagia scores before and after the procedure were recorded in both groups. The duration of relief during the follow-up period was recorded. Results: Fifty patients were enrolled in this study, including 32 patients who underwent ESP and 18 who underwent EIM. Patients in the ESP group had a markedly larger diameter of dilatation than those in the EIM group (19.9±1.8 versus 11.0±1.9 mm, respectively; P